Using fracture mechanics for determining residual stress fields in diverse geometries (2012)
Component deterioration due to a crack is of the highest importance for the engineering community. Fracture mechanics have mainly been used for studying and evaluating crack or defect nucleation and propagation. This article presents a methodology based on inducing a crack (cut) into mechanical components to characterise an induced residual stress field. This research work’s originality was aimed at highlighting fracture mechanics’ role in detecting possible component destruction by energetic analysis of crack propagation and evaluating service-life to be used as a technique for characterising the effect of prior loading history regarding a given material. The technique presented in this work is known worldwide as the crack compliance method, based on linear elastic fracture mechanics principles developed by Vaidyanathan and Finnie. Three studies are shown (bent beam, pressurised pipe and modified SEN specimen) where components were induced with a residual stress field. The way non-homogeneous loading could introduce a residual stress field is also presented; if residual stress field acting on a specimen has been characterised, then the mechanical process can be manipulated and a beneficial effect induced into the material.